Solidarity economy practices for life reproduction among Zapatista autonomous communities in Chiapas, Mexico. - Gómez Gómez, Armando (Cooperativismo & Desarrollo, 2023)
From 1994 to 2001, the struggle of the Zapatista movement in Chiapas was marked by different conversations and demands that aimed at the fulfillment of the San Andres Accords signed in 1996. When this was not achieved, the indigenous movement deepened in practice their demand for autonomy and started alternative economic initiatives, particularly as collective and cooperative systems that have developed without government support. Such practices have been little documented due to the difficulty of accessing direct information. This article presents the results of qualitative research carried out with the purpose of making visible the practices of solidarity economy, based on autonomy and resistance, in the Alteño municipality of San Andrés Larrainzar, Chiapas, detailing the importance of the Zapatista Autonomous Community Fund as a way to encourage life reproduction. It was found that these subaltern experiences based on solidarity, equity, direct democracy, and care for nature have worked not only to resist, but to build and reproduce life, generating community power capable of solving its own problems and, at the same time, setting a horizon of change facing the current destruction of capitalism.